Tianxiangdan Improves Coronary Microvascular Dysfunction in Rats by Inhibiting Microvascular Inflammation via Nrf2 Activation. (2nd December 2021) - Sawuer, Guligena; Ma, Xue-Kuan; Zhang, Ya-Jie; Zhang, Xuan-Ming; Ainiwaer, Zulihumaer; An, Dong-Qing
Abstract : Background . Tianxiangdan (TXD) is used in traditional Chinese medicine because of its therapeutic and preventive effects in the treatment of coronary heart disease. However, the underlying mechanism of TXD in coronary microvascular disease (CMD) remains unclear. Methods . A rat model of CMD was developed to study the mechanism of TXD activity. Sodium laurate was injected into the left ventricle of Sprague–Dawley rats to induce CMD. The rats were divided into six groups: a sham-operated (sham) group, an untreated CMD group, a low-dose TXD group (0.81 g·kg −1 ·d −1 ), a mid-dose TXD (TXD-M) group (1.62 g·kg −1 ·d −1 ), a high-dose TXD (TXD-H) group (3.24 g·kg −1 ·d −1 ), and a nicorandil (NCR) group (1.35 mg·kg −1 ·d −1 ). The effect of TXD on rats with CMD was observed after four weeks, and the mechanism of TXD in lipopolysaccharide (LPS)-induced cardiac microvascular endothelial cells (CMECs) was explored through treatment with 50  μ g/mL TXD. Results . Compared with the rats in the untreated CMD group, rats in the TXD-M and TXD-H groups showed higher left ventricular ejection fraction values, improved pathological structures, decreased expressions of interleukin (IL)-1 β, tumor necrosis factor-alpha (TNF- α ), phosphorylated nuclear factor- κ B inhibitor α (I κ B α ) and phosphorylated p65, and increased expressions of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (P < 0.05 ). These effects were more pronounced in the TXD-H group than in the TXD-M group. In vitro experiments showed that TXD treatment increased the viability of LPS-induced CMECs and decreased the expression of IL-1 β, TNF- α, phosphorylated I κ B α, and phosphorylated p65 (P < 0.05 ). However, the effects of TXD on CMECs were markedly reversed upon treatment with ML385 (Nrf2 inhibitor). Conclusion . The results showed that TXD exerts a protective effect on rats with CMD and related inflammatory injuries, and its anti-inflammatory mechanism is related to the activation of Nrf2 signalling.